The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1461444818799996
|View full text |Cite
|
Sign up to set email alerts
|

Learning from or leaning on? The impact of children on Internet use by adults

Abstract: Scholars have observed that children can promote Internet adoption among adults by positively influencing skills acquisition. However, it is also possible that children discourage online engagement by adults, who may lean on them to act as proxy users. Both processes have been theorized, but the net result of these opposite effects has not been empirically tested. This study provides such a test, sourcing data from large-scale surveys in six Latin American countries. The results indicate that the presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Such relationships were also revealed in the context of adults relying on children as proxy users. Galperin and Arcidiacono (2019) showed that as children’s age, educational attainment, and complexity of Internet skills and use increase, a stronger leaning effect of PIU for parents is present. Nevertheless, education seems to play a central role in PIU because, even when controlling for types of use and skills, each additional year of schooling increases the likelihood of someone being a proxy user.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such relationships were also revealed in the context of adults relying on children as proxy users. Galperin and Arcidiacono (2019) showed that as children’s age, educational attainment, and complexity of Internet skills and use increase, a stronger leaning effect of PIU for parents is present. Nevertheless, education seems to play a central role in PIU because, even when controlling for types of use and skills, each additional year of schooling increases the likelihood of someone being a proxy user.…”
Section: Discussionmentioning
confidence: 99%
“…As such, PIU involves two parties: proxy users , that is, those who “access services on another’s behalf” (Newlands et al, 2018: 2), and users-by-proxy , that is, those who receive such services through others. Although a recent study has reported that users-by-proxy are rarely “absolute non-users of the internet” (Selwyn et al, 2016: 1), PIU is predominantly being examined among Internet non-users (Dolničar et al, 2018; Eynon and Geniets, 2012; Friemel, 2016; Grošelj et al, 2019; Reisdorf et al, 2012; Van Deursen and Helsper, 2015), and many studies focus on various aspects of child–parent relationships (Correa et al, 2019; Galperin and Arcidiacono, 2019; Hänninen et al, 2018). While these studies provide important insight into demographic, social, and personal characteristics of those who seek, activate, and potentially benefit from PIU, little is known about those who provide PIU.…”
Section: Introductionmentioning
confidence: 99%
“…In lower-SES families specifically, interviews and surveys with both parents and children have revealed a "bottom-up technology transmission," during which children help their parents adopt and troubleshoot new devices (Correa et al, 2019;. Offering a counter-perspective, Galperin and Arcidiacono (2019) posit that the intergenerational transfer of skills from children to adults is outweighed by "leaning effects"decreased online engagement by adults due to proxy use by children. These authors call for further examination of children's roles in Internet adoption among low-income families specifically, and research on how digital inclusion initiatives can promote intergenerational co-engagement and skills transfer.…”
Section: Intergenerational Technology and Information Brokeringmentioning
confidence: 99%
“…Some parents reflected on how their technology skills limited their ability to address health queries on their own time and in a more private manner (e.g., on their smartphone during a bus ride), particularly when the focus of their online health information seeking involved personal or sensitive information. Parents' reflections on technology brokering thus suggest that leaning effects -decreased online engagement by adults due to proxy use by children (Galperin & Arcidiacono, 2019) -might manifest when parents opt to wait for their children's assistance rather than attempt an online search on their own. It is difficult to parse out the intentions behind such decisions, as co-searching can emerge both out of necessity and because of an inclination for collective problem solving.…”
Section: Bilingual Children Help Immigrant Parents Obtain Online Healmentioning
confidence: 99%
“…Concerning the appropriation phase of domestication, households with children have been shown to be more likely than families without children to acquire Internet access and devices to use the connection (e.g., Heim, Brandtzaeg, Kaare, Endestad, & Torgersen, 2007;Kennedy, Smith, Wells, & Wellman, 2008), mostly because children need certain devices for school-related activities (Galperin & Arcidiacono, 2019;Stevenson, 2011). Paus- Hasebrink et al (2019) even found that, regardless of parents' financial resources, all parents increase their ICT equipment when children go to school.…”
Section: 24mentioning
confidence: 99%